Competence, Training, Professionalism, and Financial Rewards Shaping Students’ Career Choice as Auditors: Kompetensi, Pelatihan, Profesionalisme, dan Penghargaan Finansial dalam Pembentukan Pilihan Karir Mahasiswa sebagai Auditor - Huda, Miftahul; Abidin, Fityan Izza Noor (Indonesian Journal of Law and Economics Review, 2024)
This study addresses the increasing demand for competent auditors by exploring how competence, professional training, and audit professionalism influence accounting students' career interest in auditing. Despite previous research on career selection, the knowledge gap lies in understanding the role of financial rewards as a moderating factor. This research aims to assess the impact of these factors while considering financial rewards as a moderator. Using a quantitative approach, data was collected from 120 accounting students from the 2020 and 2021 cohorts at Muhammadiyah University of Sidoarjo. Results indicate a positive relationship between competence, professional training, and audit professionalism with students' interest in auditing. Financial rewards were found to moderate the relationship between competence and career interest, as well as audit professionalism and career interest; however, it did not moderate professional training. The novelty of this study lies in examining financial rewards' moderating role, offering new insights for academic institutions to focus on competence and professionalism enhancement. Highlights: The study identifies financial rewards as a key factor that can strengthen the relationship between competence and students' interest in auditing careers. Professional training does not show a moderating effect with financial rewards in influencing career choices. The findings suggest a focus on competence and audit professionalism development for better career motivation. Keywords: Interest, Competence, Professional Training, Audit Professionalism, Financial Rewards